Online poetry writing at school – comparing lower secondary students’ experiences between individual and collaborative poetry writing - Kangasharju, Arja. I.; Ilomäki, Liisa; Toom, Auli (Frontiers in Education, 2024)
This study investigates how seventh-grade students experience online collaborative writing, its support in writing poems, and how collaboratively and individually written poems differ. The educational design research method was used in this mixed-methods study, which was conducted in natural classroom settings to investigate students' individual and collaborative poetry writing. The quantitative analysis of questionnaires and qualitative thematic analysis of post-experimental interviews show that the students enjoyed collaborative writing more and found it more accessible than individual writing. They experienced that it supported them in writing better poems and increased their writing confidence. They also appreciated the support of teamwork, although individual writing gave them more liberty to explore various aspects of poetry and express their feelings. From a pedagogical point of view, the students need to be provided with opportunities for collaborative poetry writing to make the writing process easier and more enjoyable. Online collaborative writing supports the process of poetry writing.